PENERAPAN METODE FUZZY MAMDANI DALAM MENENTUKAN HARGA JUAL PONSEL PINTAR BEKAS (STUDI KASUS PADA KAYYIS CELLULAR DEPOK) - Finata Rastic Andrari; Maimunah Maimunah; Nurmala Dewi Qadarsih (STEKOM PRESS, 2021)
This study discusses the application of fuzzy logic in determining the selling price of used cellphones with a case study on Kayyis Celluler Depok. This study was conducted to find out how to determine the selling price of used smart phones using the Mamdani fuzzy method approach. There are 4 fuzzy variables that will be modeled in this study, consisting of 3 input variables, namely the condition of the cellphone, market price, and cellphone accessories, and 1 output variable, namely the selling price of used cellphones. The inference process in the application of fuzzy operators uses the MIN implication function. Furthermore, the composition of all fuzzy outputs is performed using the max method. Then, confirmation or called defuzzification is done using the Centroid method.